Fuzzy multi-criteria decision making for carbon dioxide geological storage in Turkey - Deveci, Muhammet; Demirel, Nihan Cetin; John, Robert; Ozcan, Ender (ELSEVIER SCI LTD, 2015)
The problem of choosing the best location for CO2 storage is a crucial and challenging multi-criteria decision problem for some companies. This study compares the performance of three fuzzy-based multi-criteria decision making (MCDM) methods, including Fuzzy TOPSIS, Fuzzy ELECTRE I and Fuzzy VIKOR for solving the carbon dioxide geological storage location selection problem in Turkey. The results show that MCDM approach is a useful tool for decision makers in the selection of potential sites for CO2 geological storage. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Location selection; Underground carbon dioxide storage; Fuzzy decision support; Fuzzy TOPSIS; Fuzzy ELECTRE I; Fuzzy VIKOR; ANALYTIC HIERARCHY PROCESS; PLANT LOCATION SELECTION; SITE SELECTION; SUITABLE AREAS; ELECTRE METHOD; MCDM METHODS; TOPSIS; AHP; METHODOLOGY; FRAMEWORK; Energy & Fuels; Engineering